Loss of Dab2 expression in breast cancer cells impairs their ability to deplete TGF-β and induce Tregs development via TGF-β. - Shuguang Xu (PLoS ONE, 2014)
Dab2 is a multifunctional adapter protein which is frequently under-expressed in a variety of cancers. It is implicated in many critical functions, including several signaling pathways, cell arrangement, differentiation of stem cells, and receptor endocytosis. Transforming growth factor-β (TGF-β) is a secreted multifunctional protein that controls several developmental processes and pathogenesis of many diseases. It has been documented that Dab2 played an important role in TGF-β receptors endocytosis. Here, we present evidence that re-expression of Dab2 in SK-BR-3 cell partially restored its ability to deplete TGF-β in surrounding medium by normalizing the trafficking of TGF-β receptors. We also demonstrate that the difference in TGF-β depletions produced by Dab2 expression was sufficient to impact on the conversion of naive CD4+ T cells to regulatory T cells (Tregs), and thus inhibited the proliferation of T cells. This work revealed a critical result that breast cancer cell was deficient in Dab2 expression and related receptor endocytosis-mediated TGF-β depletion, which may contribute to the accumulation of TGF-β in tumor microenvironment and the induction of immune tolerance.